Gut Microbiome Composition Predicts Infection Risk During Chemotherapy in Children With Acute Lymphoblastic Leukemia. (6th March 2018) - Hakim, Hana; Dallas, Ronald; Wolf, Joshua; Tang, Li; Schultz-Cherry, Stacey; Darling, Victoria; Johnson, Cydney; Karlsson, Erik A; Chang, Ti-Cheng; Jeha, Sima; Pui, Ching-Hon; Sun, Yilun; et al.
Abstract : Gut microbiomes abundant with Proteobacteria, Enterococcaceae, or Streptococcaceae predicted infection during therapy for acute lymphoblastic leukemia. A gut microbiome biomarker may be used to stratify the infection risk in children with acute lymphoblastic leukemia before and during chemotherapy. Abstract: Background: Myelosuppression-related infections remain important causes of morbidity and mortality in children with acute lymphoblastic leukemia (ALL). Methods: By analyzing fecal samples collected at diagnosis and after each of the initial 3 phases of chemotherapy, we evaluated the role of gut microbiota in predicting infections in 199 children with newly diagnosed ALL. The bacterial 16S rRNA gene was analyzed by high-depth sequencing to determine the diversity and composition of the microbiome. Results: After the induction and reinduction I phases of chemotherapy, microbial diversity decreased significantly relative to the prechemotherapy value. After chemotherapy, the relative abundance of certain bacterial taxa (eg, Bacteroidetes) decreased significantly, whereas that of other taxa (eg, Clostridiaceae and Streptococcaceae) increased. A baseline gut microbiome characterized by Proteobacteria predicted febrile neutropenia. Adjusting for the chemotherapy phase and ALL risk level, Enterococcaceae dominance (relative abundance ≥30%) predicted significantly greater risk of subsequent febrile neutropenia and diarrheal illness, whereas Streptococcaceae dominance predicted significantly greater risk of subsequent diarrheal illness. Conclusions: In children undergoing therapy for newly diagnosed ALL, the relative abundance of Proteobacteria before chemotherapy initiation predicts development of febrile neutropenia, and domination of the gut microbiota by Enterococcaceae or Streptococcaceae at any time during chemotherapy predicts infection in subsequent phases of chemotherapy. Clinical Trial Registration: NCT00549848.